2020
DOI: 10.3390/membranes10090245
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialytic Desalination of Tobacco Sheet Extract: Membrane Fouling Mechanism and Mitigation Strategies

Abstract: In the papermaking industry (reconstituted tobacco), a large number of tobacco stems, dust, and fines are discharged in the wastewater. This high salinity wastewater rich in ionic constituents and nicotine is difficult to be degraded by conventional biological treatment and is a serious threat that needs to be overcome. Electrodialysis (ED) has proved a feasible technique to remove the inorganic components in the papermaking wastewater. However, the fouling in ion exchange membranes causes deterioration of mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…This fact, together with the need to counteract the growth of colloidal structures inside IEM and on its surface, necessitate regular cleaning of membrane stacks of ED apparatuses [26]. Most often, HCl, NaOH, hypochlorides and other oxidants (peracetic acid, and P3 Active Oxonia ® (Ecolab, Saint Paul, MN, USA) solutions) are used for these purposes [27][28][29][30][31][32][33][34]. Moreover, cleaning is carried out at a high temperature (60-90 • C) [35][36][37].…”
Section: Impact Of Traditional Cleaning Methods On the Chemical Structure Of Iemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact, together with the need to counteract the growth of colloidal structures inside IEM and on its surface, necessitate regular cleaning of membrane stacks of ED apparatuses [26]. Most often, HCl, NaOH, hypochlorides and other oxidants (peracetic acid, and P3 Active Oxonia ® (Ecolab, Saint Paul, MN, USA) solutions) are used for these purposes [27][28][29][30][31][32][33][34]. Moreover, cleaning is carried out at a high temperature (60-90 • C) [35][36][37].…”
Section: Impact Of Traditional Cleaning Methods On the Chemical Structure Of Iemsmentioning
confidence: 99%
“…IEMs conductivity, as a rule, decreases after prolonged exposure to liquid media typical for the food industry [22,23,[59][60][61]104,105]. In the case where a membrane is in contact with amino acids, carboxylic acids or anions of polybasic inorganic acids, the decrease in conductivity is not dramatic [58,104] and can be reversible if a dense layer of proteins or mineral precipitate does not form on the IEM surface [28,29,106]. The decrease in κ m is most often caused by electrostatic interactions and hydrogen bonds of foulants with fixed EIM groups.…”
Section: Interpretation Of Experimental Data Using a Microheterogeneous Modelmentioning
confidence: 99%
“…The EDS method is widely used for the identification of organic foulants or other substances on the IEM surface [81,82] (Figure 8). At the same time, drying of IEM, preceding, for example, SEM and EDS, has a destructive effect on the colloidal particles and the three-dimensional structure of most organic foulants.…”
Section: Identification Of Typical Chemical Elementsmentioning
confidence: 99%
“…In their papers, Perreault et al [ 1 ], Ge et al [ 3 ], Wang et al [ 4 ], and Abou Diab et al [ 5 ], reported the fouling of membranes by respectively polyphenols and anthocyanins (UF membrane), charged organic anions (anion exchange membranes), and divalent ions (cation exchange membrane), amino acids, and peptide or hem-peptide (cation-exchange membrane). Concerning the mechanisms, the results of the study by Ge et al [ 3 ] indicated that the membrane fouling is caused by two different mechanisms: electrostatic interactions of charged organic anions with the anion exchange membranes and precipitation of Ca 2+ and Mg 2+ on the cation exchange membrane, by reaction with OH − ions generated by water dissociation. The chemical cleaning with alkaline and acid was proposed to mitigate these fouling and scaling [ 3 ].…”
mentioning
confidence: 99%
“…Concerning the mechanisms, the results of the study by Ge et al [ 3 ] indicated that the membrane fouling is caused by two different mechanisms: electrostatic interactions of charged organic anions with the anion exchange membranes and precipitation of Ca 2+ and Mg 2+ on the cation exchange membrane, by reaction with OH − ions generated by water dissociation. The chemical cleaning with alkaline and acid was proposed to mitigate these fouling and scaling [ 3 ]. In their work, on the production of hydrolysate from bovine hemoglobin by electrodialysis with bipolar membrane (EDBM), Abou Diab et al [ 5 ] explained the fouling of perm-selective cation exchange by the fact that, according to the pH of the solution and the release of hem alone or protein fragments containing hem and peptides during hydrolysis, peptides may have first interacted electrostatically (positive residues) into the scattered cavities of the thin charged layer (forming the perm-selective layer).…”
mentioning
confidence: 99%